2006
DOI: 10.1128/jvi.80.6.3021-3029.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Nucleocapsid, Tegument, and Envelope Proteins of the Shrimp White Spot Syndrome Virus Virion

Abstract: The protein components of the white spot syndrome virus (WSSV) virion have been well established by proteomic methods, and at least 39 structural proteins are currently known. However, several details of the virus structure and assembly remain controversial, including the role of one of the major structural proteins, VP26. In this study, Triton X-100 was used in combination with various concentrations of NaCl to separate intact WSSV virions into distinct fractions such that each fraction contained envelope and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
164
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(177 citation statements)
references
References 34 publications
10
164
0
3
Order By: Relevance
“…The observations are similar to that of P. monodon (Durand et al, 1997;Wang et al, 1999;Tsai et al, 2006) except the formation of a tail like extension by the envelop. We could not find such an elongation of envelop in any of our preparation, instead fusion of trilaminar circular vesicles containing nuclear materials with the enveloped capsid was observed.…”
Section: Morphogenesissupporting
confidence: 76%
“…The observations are similar to that of P. monodon (Durand et al, 1997;Wang et al, 1999;Tsai et al, 2006) except the formation of a tail like extension by the envelop. We could not find such an elongation of envelop in any of our preparation, instead fusion of trilaminar circular vesicles containing nuclear materials with the enveloped capsid was observed.…”
Section: Morphogenesissupporting
confidence: 76%
“…Both VP37 and VP292 interacting with VP26 suggested that the similar domain of VP37 and VP292 might interact with VP26. VP26 is considered to be a tegument protein and it lies between the virus envelope and nucleocapsid [10]. VP26 was found to interact with viral nucleocapsid in vitro [14], as well as VP28 [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is an enveloped virus with a 305 kb double-stranded circular DNA genome and approximately 180 open reading frames (ORFs) [12,17]. Over 50 structural protein genes and several non-structural protein genes have been characterized [6,10,16,18]. Envelope proteins are important for virus infection and assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the smallest nucleocapsid protein was discovered in WSSV and called VP-15. It is thought to be involved in WSSV genomic packaging based on its DNA binding and condensing abilities (Ying, 2004); Tsai et al, 2006;Sangsuriya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%